(untitled) (Carte Romanze. Rivista di Filologia e Linguistica Romanze dalle Origini al Rinascimento, 2015)
Valentin et Orson fut publié d’abord à Lyon (1489, 1495), puis à Paris (ca 1511-1519). Le but de cet article est double: vérifier si le passage d’un centre éditorial à l’autre a impliqué une évolution du texte; montrer l’intérêt d’une collation systématique sur plusieurs éditions, même plus tardives, afin d’établir une édition critique. Valentin et Orson was first published in Lyon (1489, 1495), then in Paris (ca 1511-1519). This article has two aims: first, to establish whether the transfer from the former to the latter editorial centre brought with some kind of evolution of the text; second, to prove how interesting a systematic colla- tion of many editions can be, in establishing a critical edition.